1990
DOI: 10.1017/s095026880004749x
|View full text |Cite
|
Sign up to set email alerts
|

The avidity of specific IgM detected in primary rubella and reinfection

Abstract: SUMMARYAn IgM capture enzyme-linked immunosorbent assay for rubella-specific IgM was used to assess the avidity of specific IgM by comparing the results obtained with and without a mild protein denaturant in the washing fluid used after incubation of IgM with rubella haemagglutinating antigen. An avidity index (Al) was calculated with AIs < 50% considered to indicate low avidity. Sera from recent primary rubella, rubella reinfection and from patients persistently reactive for specific IgM were tested. Urea and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…With regard to low-avidity IgG in the control group, 2% of cases had low-avidity antibodies at a fairly low level (50.4%). With the exception of a slightly higher sensitivity (92.8%; 100%) (12,13), these results are comparable to others for the diagnosis of primary infection. However, they indicate less sensitivity in detecting a past infection or reinfection.…”
Section: Discussionsupporting
confidence: 84%
“…With regard to low-avidity IgG in the control group, 2% of cases had low-avidity antibodies at a fairly low level (50.4%). With the exception of a slightly higher sensitivity (92.8%; 100%) (12,13), these results are comparable to others for the diagnosis of primary infection. However, they indicate less sensitivity in detecting a past infection or reinfection.…”
Section: Discussionsupporting
confidence: 84%
“…Adaptation of the IgG ELISA for the measurement of antibody avidity Toxoplasma specific avidity was measured using the 'bind and break' method and the calculation of an avidity index [8]. Various concentrations of the hydrogen-bond disrupting agent, urea and diethylamine, were used to elute the IgG from the immobilized antigen.…”
Section: Evaluation Of the Igg Elisamentioning
confidence: 99%
“…It has been shown that the strength of the bond between antibody and individual epitopes increases with the duration of infection [7]. Measurement of the avidity of the antibody/antigen interaction has been applied to viral infections including rubella [8] and Puumala virus [9]. Recently avidity maturation has been demonstrated in patients infected with toxoplasma [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…To compensate for the reduced binding efficiency of the monomers, IgM forms oligomers ( Fig. 1) whose multiple antigenbinding sites confer high overall avidity (4). Moreover, the complex structure of IgM makes it especially effective in activating the complement system (5).…”
mentioning
confidence: 99%